Association study between CCR2-CCR5 genes polymorphisms and chronic Chagas heart disease in Wichi and in admixed populations from Argentina - Juiz, Natalia Anahí (2019)
Several studies have proposed different genetic markers of susceptibility to develop chronic Chagas cardiomyopathy (CCC). Many genes may be involved, each one making a small contribution. For this reason, an appropriate approach for this problematic is to study a large number of single nucleotide polymorphisms (SNPs) in individuals sharing a genetic background. Our aim was to analyze two CCR2 and seven CCR5 SNPs and their association to CCC in Argentina. A case-control study was carried out in 480 T. cruzi seropositive adults from Argentinean Gran Chaco endemic region (Wichi and Creole) and patients from Buenos Aires health centres. They were classified according to the Consensus on Chagas-Mazza Disease as non-demonstrated (non-DC group) or demonstrated (DC group) cardiomyopathy, i.e. asymptomatic or with CCC patients, respectively. Since, after allelic analysis, 2 out of 9 studied SNPs did not fit Hardy-Weinberg equilibrium in the unaffected non-DC group from Wichi patients, we analyzed them as a separate population. Only rs1800024T and rs41469351T in CCR5 gene showed significant differences within non-Wichi population (Creole + patients from Buenos Aires centres), being the former associated to protection, and the latter to risk of CCC. No evidence of association was observed between any of the analyzed CCR2-CCR5 gene polymorphisms and the development of CCC; however, the HHE haplotype was associated with protection in Wichi population. Our findings support the hypothesis that CCR2-CCR5 genes and their haplotypes are associated with CCC; however, depending on the population studied, different associations can be found. Therefore, the evolutionary context, in which the genes or haplotypes are associated with diseases, acquires special relevance.